Relationships between Near-Surface Horizontal Dust Fluxes and Dust Depositions at the Centre and Edge of the Taklamakan Desert - Wen Huo; Meiqi Song; Ye Wu; Xiefei Zhi; Fan Yang; Mingjie Ma; Chenglong Zhou; Xinghua Yang; Ali Mamtimin; Qing He (Land, 2022)
The emission, transport, and deposition of dust are frequently the focus of dust aerosol studies. However, owing to limited observation data, few studies have examined the relationships between the key parameters of dust transport, especially in typical dust source areas. Therefore, investigating the relationship between near-surface horizontal dust fluxes and dust depositions in typical desert source areas can further help us to understand the movement and transport patterns of dust aerosols. Based on observational experiments on two key transport parameters, this study focused on the quantitative relationship between the horizontal dust flux (Q) and dust deposition (D). A 13-month long dust sample collection experiment was conducted from August 2017 to August 2018 at Xiaotang Station (hereafter XT,40°48′ N, 84°18′ E) and Tazhong Station (hereafter TZ, 39°00′ N, 83°40′ E). The results show that the observed D and Q peaks coincided with periods of high dust storm incidence, with the greatest accumulation observed in spring. Moreover, both Q and D decreased with increasing height in XT, and this phenomenon remained on a monthly scale. In contrast, no clear decreasing pattern in Q and D with increasing height was observed in TZ. Additionally, relatively coarse particles, primarily from local sources, dominated dust depositions in both locations. The proportion of deposited dust particles with a size <20 μm was slightly higher in XT than that in TZ. Specifically, dust depositions in XT contained finer local dust particles and more dust from long-distance transport. Furthermore, D and Q had a significantly positive linear correlation in XT; however, no significant correlation was observed in TZ. Analysis of the wind dynamics and surface dust particle size indicated that topographic differences between the two stations caused these differences in correlation.